The Effect of Adding Carbon and Vanadium Carbide on Microstructure and Mechanical Properties of Ultra-Fine WC-Co Composite / Salina Budin...[et al.] - Budin, Salina; Koay, Mei Hyie; Selamat, Mohd Asri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Tungsten carbide cobalt (WC-Co) composite is commonly fabricated using powder metallurgy route such as mixing, compaction and sintering process. During the sintering process, densification of the powders takes place where WC grains having higher solubility would dissolve in the Co-rich liquid. One of the crucial aspects during sintering process is grain growth. The inappropriate sintering state will lead to an abnormal grain growth, which consequently will deteriorate the mechanical properties of WC-Co composites. Thus, a suitable grain growth inhibitor is recommended to be added in WC-Co composites to minimize the problem. In the present work, the effect of adding carbon (C) and vanadium carbide (VC) on the mechanical properties of ultra-fine WC-Co composite is investigated. The amount of Co and C is fixed at 6wt% and 0.2wt%, respectively, while the amount of VC is varied in the range of 0 to 1wt%. It is observed that, an addition of C and VC in the WC-Co composite is able to control the abnormal of grain’s growth. The relative density decreases with the increasing of wt% of VC. Similar trend is observed for hardness and transverse rupture strength (TRS). An increasing of the wt% of VC will cause excessive VC particles sited in the WC/Co grains boundary, thus hinder the liquid Co wettability to fill in the porosity between WC particles. The present of porosity will consequently permit grains growth activities. The finest grains size is achieved at the formulation 2 with 0.2wt% C and 0.4 wt% VC. The maximum hardness and TRS is attained at a similar formulation. The hardness of WC-Co composite with 0.2wt% of C and 0.4wt% of VC was approximately 40% much higher than commercial cutting insert.